Development and Promotion as Attractive Benefits: Relationships between Competences and Normative Organisational Commitment - Kowalczyk, Elżbieta; Roszyk-Kowalska, Gabriela; Cedro, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The article shows hidden, non-obvious mechanisms explaining the role of development and promotion in managing the competences of employees in public institutions which can shape normative organisational commitment (NOC). First, opinions of experts, whose task was to determine the desired level of professional competence of firefighters, were collected. Then, an original self-assessment questionnaire was developed to examine the level of social and managerial competences, as well as professional firefighters’ perception of development and promotion opportunities. Additionally, the Meyer and Allen scale was used to assess organisational commitment. Descriptive statistics were used for basic calculations and the main research used the difference test between means, the classic approach of the Baron and Kenny mediation analysis. The results obtained indicate the important role of a mediator, that is, opportunities for development and promotion which explain the relationship between the social competences of firefighters in executive positions/managerial competences of firefighters in command positions and NOC. This means that higher competences contribute to an increase in NOC, as firefighters can see opportunities for professional development and promotion. Therefore, clear and fair rules in this matter are a prerequisite for building employee–organisation relations.